Effects of steel fibres and prestress levels on behaviour of newly proposed exterior dry joints using SFRC and CFRP bolts - Tuan T. Ngo; Thong M. Pham; Hong Hao (My University, 2020)
Effects of steel fibres and prestress levels on behaviour of newly proposed exterior dry joints using SFRC and CFRP bolts
Keywords: Bê tông cốt sợi thép; CFRP bolts; Mối nối khô